Examination of the ethical positions of philosophy group teachers and their perception of metaphors related to the concept of ethics - Duygu Göktaş; Birsel Aybek (Anadolu Üniversitesi Eğitim Fakültesi dergisi)
The Ethical Concept has been a topic that has not lost its relevance throughout history. That is why it is an indispensable subject of research. The teachers of the philosophy group have a conceptual substructure regarding the concept of ethics. This substructure forms the ideology and perceptions of the philosophical group of teachers regarding the concept of ethics. Many studies have been conducted on ethics, including those of teachers, directors, and students. In literature, however, there is no study of a philosophical group to ensure that the concept of ethics is the subject of teaching. Based on the reasons stated, this study aims to examine the metaphorical perceptions of ethical status levels and the concept of ethics by the teachers of the philosophy group. The study was carried out using the parallel method of synchronization, with 107 philosophical group teachers working in the central districts of Adana, Çukurova, Sarıçam, Seyhan and Yüreğir in the educational year 2020-2021. Sample selection based on maximum diversity was made to determine participants. The study used the personal information form as a tool for data collection, the Ethics Position Questionnaire developed by Forsyth (1980), and the metaphor for the ethical concept developed by researchers. Quantitative data were analyzed using the SPSS 22 program. Qualitative data is dealt with together with metaphors and reasoning by means of content analysis. In the subsequent process, the qualitative and quantitative data sources were analyzed first separately and then jointly, and the analysis found that the demographic structure had no impact on ethical position levels, and that the sub-dimension of idealism was high on the ethical state levels of the participants compared to the relativistic sub-dimension. Participants produced a total of 68 different metaphors. The most widely used metaphor by the teachers of the philosophy group has been identified as the concept of "human". In addition, they consider the concept of ethics to be the most guiding and vital element.